Morphological variations in pulmonary atresia with intact ventricular septum. - Zuberbuhler, J R (1979)
The morphological features of a series of 37 specimens of pulmonary atresia with intact ventricular septum were reviewed with particular emphasis on features which might influence the results of pulmonary valvotomy. The degree of right heart hypoplasia was quantified by measuring right and left heart dimensions and comparing them with 20 normal infant hearts. Right ventricular cavity size was usually smaller than normal but constituted a spectrum ranging from tiny to a dilated ventricle larger than normal. There was a positive correlation between triscuspid annular size and right ventricular size but no correlation between the size of the pulmonary artery and the right ventricle. Successful pulmonary valvotomy with subsequent adequate right ventricular function would have been precluded by a tiny right ventricular cavity or infundibular atresia in 14 specimens and by severe tricuspid stenosis or regurgitation in an additional 4. Severe right or left ventricular endocardial fibroelastosis may have adversely affected ventricular function in several others. Ten specimens displayed convex bulging of the left ventricular septal surface. If these these anatomical findings are representative for the condition as a whole, they provide a good explanation for its disastrous prognosis.